Preferred beer styles influence both perceptual maps and semantic descriptions of dry hops. (December 2021) - Hopfer, Helene; McDowell, Elliott H.; Nielsen, Line E.; Hayes, John E.
Highlights: Two consumer cohorts – craft beer drinkers and light beer drinkers – were recruited. Perceptual Maps of hop cones were created via Free Sorting for each cohort. After sorting, hop groupings were characterized semantically using a CATA task. Perceptual maps across groups showed little agreement. The light beer drinkers used fewer descriptors to describe their groupings. Abstract: Hops, the flowers of the Humulus lupus plant, are almost exclusively used in beer production, where they add important flavor qualities, such as bitter taste and a variety of aromas, to the finished product. Depending on concentration, variety, and time of addition, different beer styles are created, appealing to a broad range of consumer needs. Consumers of different beer styles both state and reveal a strong preference for their respective preferred style, presumably due to their familiarity with unique aromas and flavors experienced with different beer styles. Here we use several rapid profiling methods – free sorting (FS) in combination with check-all-that-apply (CATA) – to perceptually characterize nine samples of hops (7 varieties; 2 blind duplicates; all whole hops cones) with naïve participants who had been segmented by their typical beer consumption habits (craft versus light beer consumers). The 'light' group (n = 30) exclusively consumed light, American lager beer styles while the 'craft' group (n = 32) exclusively consumed what they considered 'craft' or 'micro-brew' beers, which are typically associated with more intense hop flavors. All participants were asked to first sort the whole hop cone samples into groups based solely on perceptual similarity; they were then asked to endorse a list of 24 common hops aroma descriptors in a CATA task. Sorting data were used to generate perceptual maps via DISTATIS. Inspection of the perceptual maps indicate participants successfully differentiated between hop samples, and no differences in the number of groups formed between the two consumer groups were found; however, the two cohorts grouped hops samples differently, and resulting maps showed little agreement. Further, the light beer drinkers checked significantly fewer attributes in the CATA task to describe their groupings of hop cones and were also less discriminating between the hops cones relative to the craft beer consumers. These data suggest free sorting can be used to profile hops, and observed differences between types of beer drinkers are both perceptual and linguistic in nature.